2020
DOI: 10.3889/oamjms.2020.3984
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Propolis Reduces Malondialdehyde Level and Increase Osteoblast Cell Number in Wistar Rats with Orthodontic Tooth Movement

Abstract: AIM: The aim of this study was to determine the antioxidant activity of Indonesian propolis gel 5% in Wistar rats alveolar bone, toward malondialdehyde serum levels and osteoblast cells number caused by orthodontic tooth movement (OTM). METHODS: This was an experimental study using the post-test only group design. The samples were 28 male Wistar rats, divided into four groups: G1 (control group) – group without OTM and without propolis, G2 – group without OTM and with propolis, G3 – group with OTM and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Propolis also reduced bone resorption at the alveolar bone, as evidenced by decreased osteoclast number [50,51]. In another study by Wiwekowati et al [52], propolis treatment (5% propolis gel for 17 days) showed increased osteoblast number in the alveolar bone of rats with OTM. Propolis also reduced oxidative damage, as evidenced by decreased lipid peroxidation product, MDA, in the blood [52].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Propolis also reduced bone resorption at the alveolar bone, as evidenced by decreased osteoclast number [50,51]. In another study by Wiwekowati et al [52], propolis treatment (5% propolis gel for 17 days) showed increased osteoblast number in the alveolar bone of rats with OTM. Propolis also reduced oxidative damage, as evidenced by decreased lipid peroxidation product, MDA, in the blood [52].…”
Section: Discussionmentioning
confidence: 87%
“…In another study by Wiwekowati et al [52], propolis treatment (5% propolis gel for 17 days) showed increased osteoblast number in the alveolar bone of rats with OTM. Propolis also reduced oxidative damage, as evidenced by decreased lipid peroxidation product, MDA, in the blood [52]. RME is a common orthodontic procedure to increase the transverse width of the maxillary basal bone but studies have reported root resorption following the procedure [54,67].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations